Association Between Free-Living Sit-to-Stand Transition Characteristics, and Lower-Extremity Performance, Fear of Falling, and Stair Negotiation Difficulties Among Community-Dwelling 75 to 85-Year-Old Adults. Issue 8 (21st March 2022) - Löppönen, Antti; Karavirta, Laura; Koivunen, Kaisa; Portegijs, Erja; Rantanen, Taina; Finni, Taija; Delecluse, Christophe; Van Roie, Evelien; Rantalainen, Timo
Abstract: Background: Good sit-to-stand (STS) performance is an important factor in maintaining functional independence. This study investigated whether free-living STS transition volume and intensity, assessed by a thigh-worn accelerometer, is associated with characteristics related to functional independence. Methods: Free-living thigh-worn accelerometry was recorded continuously for 3–7 days in a population-based sample of 75-, 80-, and 85-year-old community-dwelling people (479 participants; women n = 287, men n = 192). The records were used to evaluate the number and intensity (angular velocity of the STS phase) of STS transitions. Associations with short physical performance battery (SPPB), 5-times-sit-to-stand test (5×STS), isometric knee extension force, self-reported fear of falls, and self-reported difficulty in negotiating stairs were also assessed. Results: The number of STS transitions, mean and maximal angular velocity were lower in older age groups ( p < .05). All variables were higher in men than in women ( p < .001) and were positively associated with SPPB total points, knee extension force ( r ranged from 0.18 to 0.39, all p < .001) and negatively associated with 5×STS ( r = −0.13 – −0.24, all p < .05), lower extremity functional limitations ( p < .01), fear of falls ( p < .01), and stair negotiation difficulties ( p < .01). Conclusions: Free-living STS characteristics were related to lower-extremity performance, lower extremity functional limitations, self-reported fear of falls, and stair negotiation difficulties, which can be a sensitive indicator of impending functional decline. Moreover, STS transitions may provide an indicator of adequacy of lower-limb muscle strength among older individuals.